Glomerular Filtration Rate Assessment in Children - Sonja Golob Jančič; Mirjam Močnik; Nataša Marčun Varda (Children, 2022)
Glomerular filtration rate (GFR) measurement is a key tool for determining the degree of chronic kidney disease. The assessment of GFR is even more challenging in children than in adults with more variables in the equation than race and sex. Monitoring the progress of the kidney disease can therefore be difficult as in the initial stages of a decline in kidney function, there are no clinical signs. Due to children’s growth and development, changes in muscle mass and growth impair GFR estimation based solely on serum creatinine values. More invasive methods of GFR measurement are more reliable, but techniques using ionising agents, requiring large volume blood samples or timed voiding, have limited application in children. This paper reviews the methods of measuring and determining glomerular filtration rate and kidney function in children.